Iron(III)/TEMPO-Catalyzed Synthesis of 2,5-Disubstituted 1,3,4-Oxadiazoles by Oxidative Cyclization under Mild Conditions - Zhang, Guofu; Yu, Yidong; Zhao, Yiyong; Xie, Xiaoqiang; Ding, Chengrong (Synlett, 2017)
A simple and efficient cationic Fe(III)/TEMPO-catalyzed oxidative cyclization of aroyl hydrazones has been developed for the synthesis of 2,5-disubstituted 1,3,4-oxadiazole derivatives. The reaction offers a broad scope, good functional-group tolerance, and high yields under mild conditions in the presence of O2.
Keywords: oxadiazoles; iron catalysis; cyclization; oxidation; aroyl hydrazones